Modulated fees for Extended Producer Responsibility schemes (EPR) - Laubinger, Frithjof (OECD Environment Working Papers, 2021)
One of the key objectives of Extended Producer Responsibility (EPR) is to instigate design for the environment. In collective EPR schemes, the fee schedule set by Producer Responsibility Organisations (PROs) is typically quite simple and provides weak incentives for design change by producers. Fee modulation, changing fees paid by producers in a collective EPR scheme based on product design, can provide producers with stronger design incentives, but adds complexity to the system. The paper defines a classification for fee modulation (by criteria and methodology) and discusses potential challenges and opportunities. It concludes with key policy insights that can further stimulate this emerging policy approach